Influence of Authentic Leadership and Work Motivation on Organizational Commitment with Job Satisfaction as a Variable Mediation at RSUD Dr. M. Yunus Bengkulu - Sapri , Muhammad Falah (Student Journal of Business and Management, 2024)
The objective of this research is to analyze the effect of online customer reviews and ratings on purchasing decisions on Shopee e-commerce with trust as a mediator and emotions as a moderator. The research method used is quantitative, and primary data was collected by online questionnaires. The population in this study are Shopee e-commerce users. Participabts in this research concisted of 217 respondents in Indonesia. The sampling technique uses purposive sampling. The method of analysis this study using Lisrel 8.8 is analysis with a variance-based structural equation modeling approach. The findings reveal that the: 1) online customer reviews have a positive effect on purchasing decisions. 2) online customer ratings have a negative effect on purchasing decisions. 3) online customer reviews have a positive effect on trust. 4) online customer ratings have a positive effect on trust. 5) trust has a positive effect on purchasing decisions. 6) the mediating role of trust between online customer review variables on purchasing decisions has an influence that has a partially mediated mediating role. 7) the mediating role of trust in mediating online customer assessments of purchasing decisions has a full mediating role. 8) emotional variables cannot moderate online customer review variables on purchasing decisions.